Fourth Five Year Plan a Draft Outline Part I-Approach and Policy - Planning Commission (Planning Commission, 1966)
This Draft Outline sets out the substance of the proposals of the Planning Commission for the Fourth Five Year Plan. It is being offered for consideration by Parliament and State Legislatures and for eliciting the views of all sections of public opinion. It is .also intended to assist the Central .Ministries, State Governments and various other concerned organisations in the country in working out their detailed proposals for the Fourth Plan. After taking these into consideration, a final report of the Fourth Five Year Plan will -be submitted to Parliament for approval a few: months, later. This Outline gives only the broad contours of the proposed Plan and briefly mentions some of. the policy.issues involved. These will be elaborated and dealt with more fully in the final report.
Government of India Planning Commission